The Use of Code Switching in Twitter (A Case Study in English Education Department) - Widya Novianti (Universitas Pendidikan Indonesia (UPI), 2013)
This study explores some important issues, namely the occurrences of code switching types, languages used, and the reasons why the respondents switch their language in communicating in Twitter. The study involved the students of English Education Department who had already signed up as Twitter users as the respondents. In this study, the data were the tweets used by the respondents and the responses of the questionnaires. To identify code switching types in the tweets, Poplack’s framework (1980) was applied. Moreover, the theories proposed by Hoffman (1991) and Saville-Troike (1986) were used as the basis of interpretation to investigate the reasons why the respondents switch their language in Twitter. The data (selected tweets and questionnaires) were analyzed by several steps, namely identifying the occurrences of code switching from the tweets, classifying the code switching in the form of tables, quantifying the frequency and the percentage of code switching, and analyzing and discussing the data obtained. The results show that there are three types of code switching, seven language combinations and six reasons of the use of code switching in Twitter. In terms of the type, intra-sentential switching tends to be the most frequent type of code switching (56.67%). In relation to language combinations used in the tweets, Indonesian-English is likely to be the most frequent language combination (73.33%). Moreover, in relation to the reason, real lexical need may be considered as the main reason to switch the language in Twitter (60%). Keywords: Code Switching, Twitter, Twitter Users, Tweets